2014
DOI: 10.1186/1471-2431-14-25
|View full text |Cite
|
Sign up to set email alerts
|

Body composition variables as predictors of NAFLD by ultrasound in obese children and adolescents

Abstract: BackgroundNonalcoholic fatty liver disease (NAFLD) is a disorder associated with excessive fat accumulation, mainly in the intra-abdominal region. A simple technique to estimate abdominal fat in this region could be useful to assess the presence of NAFLD, in obese subjects who are more vulnerable to this disease. The aim of this cross-sectional study was to verify the reliability of waist circumference and body composition variables to identify the occurrence of NAFLD in obese children and adolescents.MethodsS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 28 publications
5
43
0
1
Order By: Relevance
“…However, in the study of Motamed et al, similar to our study, the AUC of FLI was almost similar to WC (25). This can be due to abdominal fat, and so WC is an important factor in predicting NAFLD (26).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 30%
“…However, in the study of Motamed et al, similar to our study, the AUC of FLI was almost similar to WC (25). This can be due to abdominal fat, and so WC is an important factor in predicting NAFLD (26).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 30%
“…Furthermore, Peng et al (8) showed that the liver expressed the highest levels of betatrophin in humans, whereas expression was lower in adipose tissue and skeletal muscle. Additional studies demonstrated that hyperinsulinaemia could accelerate NAFLD in obesity, which subsequently might result in insulin resistance via mechanisms including inflammation and unsaturated fatty acids (24,32,33). Moreover, the prevalence of NAFLD in the insulin-resistant group was significantly higher than that in the non-insulin-resistant group.…”
Section: Discussionmentioning
confidence: 99%
“…NAFLD is a disease associated with excessive accumulation of fat, particularly within the abdominal cavity. Monteiro et al in a research conducted in a sample composed of 145 subjects, aged 11 to 17 years, pointed out the usefulness of indicators such as assessment of waist circumference (WC), trunk fat mass (TFM) and fat mass (FM) by dual-energy X-ray absorptiometry (DXA) and ultrasound (US) for diagnosis of NAFLD [51]. Their findings indicated that TFM, IAAT and WC present high potential to identify NAFLD in obese children and adolescents.…”
Section: The Occurrence Of the Metabolic Syndrome In Children With Amentioning
confidence: 99%
“…Indicators such as assessment of waist circumference (WC), trunk fat mass (TFM), fat mass (FM) by dual-energy X-ray absorptiometry (DXA) and ultrasound (US) are useful for diagnosis of NAFLD [51].…”
Section: Conclusion and Summarymentioning
confidence: 99%